A synthesis of cordierite from aluminium slag - Junlar, Pranee; T.saengechantara, Wanna; Rugthaicharoencheep, Sansanee (Bulletin of Applied Sciences, 2022)
This research focused on the synthesis of cordierite from aluminum slag to produce kiln furniture. The compositions based on an industrial Al-rich sludge, kaolin, ball clay, talc, and quartz at sintering temperatures of 1250, 1280, and 1300 °C. The properties of synthesized cordierite, namely phase compositions by means of X-ray diffraction (XRD), physical properties, strength (Modulus of Rupture), and thermal expansion coefficient were evaluated. The XRD analysis confirmed that the major phase of sample synthesized at 1300 °C was cordierite. The sample had firing shrinkage between 8.1-9.9%, water absorption in the range of 13.8-16.8%, density (Bulk density) between 1.80-1.88 g/cm³ , strength between 20.7-22.7 MPa, and thermal expansion coefficient in the range of 3.199—3.694 x 10-6/°C. In addition, the composition with the highest cordierite phase and strength were selected to form a V-shape, 5 cm high kiln furniture prototype using a slip casting method.lease the fragrance.